Salicylic acid-induced germination, biochemical and developmental alterations in rye (Secale cereale L.) - ÇETİNBAŞ GENÇ, ASLIHAN (UNIV ZAGREB, FAC SCIENCE, DIV BIOLOGY, 2018)
Salicylic acid (SA) is one of the endogenous plant growth regulators that modulate various metabolic and physiological events. To evaluate the exogenous SA-induced germination, biochemical and developmental alterations, different concentrations (10, 100, 500 and 1000 mu M) of SA were applied to rye (Secale cereale L.) seeds in hydroponic culture conditions for 15 days. The observations revealed that seed germination and root elongation were stimulated in 10 mu M SA treatment, however they were inhibited in higher concentrations (100 and 500 mu M) of SA. Furthermore, there was no germination in 1000 mu M SA. The analysis of antioxidant enzymes revealed that although superoxide dismutase activity increased, catalase activity decreased in comparison to control. Besides, lipid peroxidation and peroxidase activity increased in 10 mu M SA, whereas they decreased in higher concentrations. Similarly total chlorophyll content increased in 10 mu M SA, but it decreased in 100 and 500 mu M SA treatments. Moreover anthocyanins and carotenoids increased after SA treatment. In conclusion, exogenous SA application causes developmental and biochemical alterations in rye.
Keywords: antioxidant enzyme; lipid peroxidation; photosynthetic pigments; salicylic acid; ABIOTIC STRESS TOLERANCE; OXIDATIVE STRESS; SUPEROXIDE-DISMUTASE; WHEAT SEEDLINGS; ACTIVE OXYGEN; ARABIDOPSIS; GLUTATHIONE; INDUCTION; GROWTH; DAMAGE